(untitled) (London Journal of Research In Humanities and Social Sciences, 2022)
This research project was to study the results of applying Knowledge Management (KM), through applying participatory action research, sufficiency economy philosophy growing phak waan pah vegetable for the development of knowledge managers at self-reliance learning centers in Thailand. The development model comprised 19 sub-courses which focused on practical skill development. Participants were 15 knowledge managers from 2 self-reliant centers in Maha Sarakham, and Khon Kaen province. The skill and knowledge development course lasted 4 days and 3 nights and then the participants applied the gained knowledge at self-reliance centers for the subsequent 4-6 months. Overall, the development course yielded success with the efficiency of knowledge output of 88.94 / 83.22. The effectiveness index was 0.7178 which explained the resource leader’s higher knowledge 71.78%. Participants of the project who have a farm area of approximately 1-3 rais had a substantial debt reduction and were able to generate income from harvesting phak waan pah for 6-8 months per year. The farmers are able to get 150-200 Baht per kilogram of phak waan pah and have an earning potential of over 100,000 baht per year. The participants entered the project as volunteers but became knowledge managers in self-reliance through PAR, and have a sustainable development future in accordance with the philosophy of the sufficiency economy.